Transporters, channels and human disease. - Ashcroft, F; Röper, J (1993)
The past year has seen significant advances in our understanding of the molecular biology of ion channels and transporters and their role in human disease. The star of the show has to be the cystic fibrosis chloride channel about which an enormous amount of information has been accumulated, and the functional effects of some of the mutations found in cystic fibrosis patients have been characterized.